Capsular warning syndrome and its clinical awareness and therapeutic approach: two case reports and a systematic review of the literature - Martínez, Hector R.; Figueroa-Sanchez, Jose A.; Arreola-Aldape, Carlos A.; Moran Guerrero, Jose Alberto; Trujillo-Bracho, Ana Luisa; Cantú López, Alejandro (Frontiers in Neurology, 2023)
Introduction Capsular warning syndrome (CWS) is characterized by recurrent stereotyped episodes of unilateral transient motor and/or sensory symptoms affecting the face and upper and lower limbs, without cortical signs in 24 h and with a high risk of developing stroke. Among the possible underlying mechanisms, small perforating artery disease is the most common. The aim was to assess the most common risk factors, the therapeutic alternatives, and the different outcomes in patients with CWS, along with the presentation of two cases treated in our Emergency Department. Methods Stroke Code, launched at our institution in January 2017, was triggered 400 times, and by December 2022, 312 patients were admitted as having an acute ischemic stroke. Among them, two of them fulfilled the criteria of CWS. A systematic search was carried out in PubMed, Scopus, and Web of Science databases to seek demography and therapeutic approaches in CWS. Results Of 312 cases, two with acute ischemic stroke exhibited CWS. The first patient had six events of right hemiparesis with recovery in 10–30 min; after MRI and digital subtraction angiography (DSA), he received apixaban and clopidogrel; however, a day after admission, he developed ischemic infarction with partial recovery. The second patient presented five transient events of right hemiparesis. After MRI and DSA with an intra-arterial infusion of nimodipine, oral aspirin, and ticagrelor, he presented another event-developing stroke and was discharged with partial recovery. A systematic review found 190 cases of CWS in 39 articles from 1993 to 2022. Most were male subjects (66.4%), and hypertension (60%), smoking (36%), diabetes (18%), and dyslipidemia (55%) were the most common risk factors. Over 50% of the cases were secondary to small perforating artery disease. The most commonly used treatments were dual antiplatelet therapy (DAT), recombinant tissue plasminogen activator, and anticoagulant therapy (ACT), where the combination of DAT plus ACT was linked to the most positive functional outcomes (82.6%). Conclusion Our cases fit with the description of patients with partial recovery and risk factors (hypertension, diabetes, and smoking) in male patients. There is a lack of evidence regarding the best treatment option; dual antiplatelet therapy and anticoagulation therapy are strong contenders for a favorable result.